Low-Fat Salad Dressing as a Potential Probiotic Food Carrier Enriched by Cold-Pressed Tomato Seed Oil By-Product: Rheological Properties, Emulsion Stability, and Oxidative Stability - Akcicek, Alican; Yildirim, Rusen Metin; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih (AMER CHEMICAL SOC, 2022)
This study aims to investigate the potential of the use of cold-pressed tomato seed oil by-products in a low-fat salad dressing as potential probiotic food carriers to improve the oxidative stability and emulsion stability as well as the rheological properties. The low-fat salad dressing emulsions were formulated with cold-pressed tomato seed by-product (TBP) and Lactobacillus plantarum ELB90. The optimum low-fat salad dressing formulations found were determined as 10 g/100 g oil, 0.283 g/100 g xanthan, and 2.925 g/100 g TBP. The samples prepared with the optimum formulation (SD-O) were compared with the low-fat control salad dressing sample (SD-LF) and the high-fat control salad dressing sample (SD-HF) based on the rheological properties, emulsion stability, oxidative stability, and L. plantarum ELB90 viability. The sample SD-O showed shear-thinning, viscoelastic solid, and recoverable characters. The sample SD-O showed higher IP and Delta G++ and lower Delta S++ values than those of the control samples. After 9 weeks of refrigerated storage, viable L. plantarum ELB90 cell counts of salad dressing samples were counted as 7.93 +/- 0.03, 5.81 +/- 0.04, and 6.02 +/- 0.08 log cfu g-1 for SD-O, SD-LF, and SD-HF, respectively. This study showed that TBP could be successfully used in a low-fat salad dressing as a potential probiotic carrier.
Keywords: ANTIOXIDANT ACTIVITY; MAYONNAISE; OPTIMIZATION; FORMULATION; BEHAVIOR; PHENOLS; Chemistry